Optimasi Proses Karbonisasi Tandan Kosong Sawit Menggunakan Response Surface Methodology - Putra, Bayu Eldino; Helwani, Zuchra; Fatra, Warman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Empty fruit bunches (EFB) is a source of biomass which has not been utilized optimally yet. EFB can be used as source of solid fuel in the form of charcoal because of its high calorific value 18,200.75 kJ / kg. The calorific value can be increased by carbonization. Carbonization is a process to convert lignoselulose biomass into charcoal within temperature range 300 – 600 °C in a limited oxygen environment. The purpose of this research is to utilize EFB as a source of solid fuel, to study the effect of process condition such as temperature, holding time, and feed size towards the characteristics of resulted charcoal and to optimize carbonization process from the data obtained. Reactor used for EFB carbonization is a tube furnace at operating conditions of temperature (350, 400 and 450 °C), holding time (90, 120 and 150 minutes) and feed size (2, 4 and 6 cm). Responses were analyzed, namely the calorific value and volatile matter by using Response Surface Methodology (RSM). Optimum conditions obtained are temperature 450 °C, holding time 90 minutes and feed size 6 cm with calorific value 28,106 kJ/kg and volatile matter 13.47 %. The most influential process variable for calorific value is temperature. Meanwhile for volatile matter, every process variables give significant effect.Keywords : Carbonization, Calorific Value, Empty Fruit Bunch, Optimization, RSM